Digital Versus Classic Goniometry in Shoulder Motion Evaluation: An Agreement Pilot Study - Couto Amorim, Hugo; Serviço de Medicina Física e de Reabilitação do Centro Hospitalar de São João,Porto, Portugal (2017)
Introduction: Shoulder range of motion measurement is not only of diagnostic significance but is also relevant for monitoring response to therapeutic interventions. Smartphones incorporate accelerometers which enable easy multiaxial and multiangle measurements but their reliability compared to the classic goniometer remains to be established. The authors aim to ascertain the intra-rater reliability between manual and smartphone-based digital goniometry in measuring active flexion and external rotation in both standing and supine positions.Methods: A convenience sample of 16 healthy volunteers was selected. Measures were taken by an independent rater at two different times, a week apart. We randomized both participant’s order and measurement sequence. The rater was trained according to a predetermined measurement protocol and blinded to intermediate measurements. We evaluated agreement between methods using the intraclass correlation coefficient, visual inspection of Bland-Altman plots and calculation of the limits of agreement.Results: The intra-rater correlation was good regarding the external rotation-standing intraclass correlation coefficient 0.87 (IC 95%: 0.66-0.95), the external rotation-supine intraclass correlation coefficient 0.92 (IC 95%: 0.80-0.97)) and the active flexion standing intraclass correlation coefficient 0.92 (IC 95%: 0.78-0.97). The score was lower in the active flexion supine intraclass correlation coefficient 0.81 (IC 95%: 0.55-0.93).Conclusion: There was a good intra-rater reliability between classic and digital goniometer in external rotation (regardless of positioning) and in standing active flexion. The smartphone based digital goniometer might be an easy tool to assist physical examination in healthy individuals, but its accuracy and applicability to clinical settings needs further evaluation.